Niederdeutsch in Westfalen. Ein historisches digitales Textkorpus - Robert Peters; Norbert Nagel (Filologia Germanica)
The project ‘Low German in Westfalia’, conducted at the Universities of Münster and Bielefeld, addresses the documentation of Low German texts from the ancient Westfalian speaking region. Texts relevant for this project date from the 9th century to the middle of the 19th century. The project assembles a digital corpus of texts, both manuscripts and printed books, covering all fields of written language: 1. administration, 2. legislation, 3. texts to support (scientific) knowledge transfer, 4. religious literature, 5. profane literature, 6. private texts, 7. inscriptions. Most texts belong to the Late Middle Ages and Early Modern Age. The digital archive forms a basis for further exploration of historical texts in Westfalian-Low German. Planned to cover a seven-year span, the Westfalia-project corpus can be used online by experts as well as by non-experts while the project is in progress and afterwards.